Oil, National Wealth, and Current and Future Consumption Possibilities - Tersman, Gunnar (IMF Working Papers; Working Paper, 1991)
This paper offers a discussion about the macroeconomics of exhaustible resources. In a resource-based economy, long-term sustainability is an obvious issue. This paper outlines some ideas on how to treat issues related to exhaustible resources in a macroeconomic context. Based on a small dynamic general equilibrium model, the approach is demonstrated with the help of some simple numerical examples.